Terminalia catappa IN ORNAMENTAL AQUACULTURE: A PHYTOTHERAPEUTIC INNOVATION AGAINST ANTIMICROBIAL RESISTANCE (REMUNOM, 2025)
Ornamental fish farming represents a prominent sector in global aquaculture, generating billions of dollars and playing an important socioeconomic role. However, increased fish farming density and inadequate sanitary management favor the occurrence of bacterial diseases, especially those caused by Aeromonas spp., leading to the recurrent use of synthetic antimicrobials. This scenario has contributed to the emergence of resistant strains and adverse environmental impacts, requiring safer and more sustainable therapeutic alternatives. In this context, the use of medicinal plants emerges as a promising strategy, particularly Terminalia catappa, a species widely distributed in tropical regions and recognized for its pharmacological properties. Studies report that almond leaf extracts are rich in phenolic compounds, tannins, flavonoids, and terpenes, responsible for antioxidant, antimicrobial, and immunomodulatory effects in ornamental fish. The application of the leaves or their extracts improves water quality, reduces stress, increases resistance to pathogens, and can partially replace the use of synthetic antibiotics. Thus, T. catappa stands out as a natural and ecological alternative for the health management of ornamental aquaculture, contributing to the productive and environmental sustainability of the sector.